Abnormal blink reflex recovery cycle in manifesting and nonmanifesting carriers of the DYT1 gene mutation. Issue 14 (28th September 2016) - Fong, Po-Yu; Edwards, Mark J.; Lu, Chin-Song; Chen, Rou-Shayn; Rothwell, John C.; Bhatia, Kailash P.; Huang, Ying-Zu
Abstract : The aim of this study is to evaluate the brainstem function in DYT1 carriers manifesting clinical dystonia (MDYT1) and those without clinical symptoms (NMDYT1). Motor cortical inhibition and plasticity were found to be abnormal in MDYT1, whereas these were less abnormal in NMDYT1. However, the spinal reciprocal inhibition was abnormal in MDYT1, but normal in NMDYT1. Moreover, protein accumulation and perinuclear inclusion bodies were found in the brainstem, but not in other brain areas, in DYT1 patients. Therefore, we designed this study to investigate the brainstem physiology using the blink reflex (BR) recovery cycle test in MDYT1 and NMDYT1. We recruited eight MDYT1, five NMDYT1, and nine age-matched healthy controls. The BR recovery cycle was assessed with paired stimuli that induced the BR in a random order at interstimulus intervals of 250, 500, and 1000 ms. A two-way analysis of variance showed a significant difference between MDYT1, NMDYT1, and the healthy control ( P =0.004). Post-hoc analysis showed that this was because of a significantly lower inhibition of R2 in MDYT1 and NMDYT1 compared with the controls (two-way analysis of variance: P =0.003 and 0.021, respectively). There was no difference between MDYT1 and NMDYT1 ( P =0.224). The tested brainstem circuits were equally involved in MDYT1 and NMDYT1. The finding is in agreement with the pathological findings in DYT1 carriers. Together with previous findings in the motor cortex and the spinal cord, the brainstem may lie closer to the pathogenesis of dystonia than the motor cortex in DYT1 gene carriers.